Quantifying the Ripple Effects of Civil War: How Armed Conflict Is Associated with More Severe Violence in the Home - Jocelyn T. D. Kelly; Elizabeth Colantuoni; Courtland Robinson; Michele R. Decker (Harvard FXB Center for Health and Human Rights, 2020)
Both the fields of public health and that of human rights seek to improve human well-being, including through reducing and preventing all forms of violence, to help individuals attain the highest quality of life. In both fields, mathematical methods can help "visibilize" the hidden architecture of violence, bringing new methods to bear to understand the scope and nuance of how violence affects populations. An increasing number of studies have examined how residing in a conflict-affected place may impact one of the most pervasive forms of violence-intimate partner violence (IPV)-during and after conflict. This paper contributes to this effort by examining whether severe forms of IPV are associated with previous experience of political violence in one conflict-affected country: Liberia. Our findings indicate that living in a district with conflict fatalities increased the risk of IPV among women by roughly 60%. Additionally, living in a district with conflict fatalities increased the risk of a past-year injury from IPV by 50%. This analysis brings to light links between two of the most pervasive forms of violence-political violence and violence against women. The findings suggest that women residing in a district that is more highly affected by conflict, not only people experiencing direct trauma during conflict, may be at risk of increased violence long after peace is declared. These findings point to the need for targeted programs that address IPV postconflict.